2020
DOI: 10.1186/s12886-020-01721-5
|View full text |Cite
|
Sign up to set email alerts
|

Preloaded vs manually loaded IOL delivery systems in cataract surgery in the largest ambulatory surgery center of northwestern China: an efficiency analysis

Abstract: Background To compare the efficiency of preloaded vs manually loaded IOL (P-IOL vs M-IOL, respectively) delivery systems in cataract surgery in the largest ambulatory surgery center of Northwestern China. Methods A total of 200 cases were included in this prospective, observational study. Time and motion data were collected in a one- or two-operating room (1-OR or 2-OR, respectively) scenario. A model of the efficiency and revenue implications of introducing a preloaded delivery system for IOLs in cataract su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Recent publications have reinforced that preloaded monofocal hydrophobic acrylic IOLs provide an opportunity to make cataract surgery quicker, easier, safer, and therefore more economical. A recent observational study involving 200 routine cataract surgeries showed a significantly decreased mean total case time by 7.7–7.8% when using a preloaded monofocal hydrophobic acrylic IOL rather than a manual IOL delivery process [ 17 ]. Preloaded monofocal hydrophobic acrylic IOLs have also performed well in recent studies involving challenging cases of pseudoexfoliation syndrome [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have reinforced that preloaded monofocal hydrophobic acrylic IOLs provide an opportunity to make cataract surgery quicker, easier, safer, and therefore more economical. A recent observational study involving 200 routine cataract surgeries showed a significantly decreased mean total case time by 7.7–7.8% when using a preloaded monofocal hydrophobic acrylic IOL rather than a manual IOL delivery process [ 17 ]. Preloaded monofocal hydrophobic acrylic IOLs have also performed well in recent studies involving challenging cases of pseudoexfoliation syndrome [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with manually loaded IOLs, preloaded delivery systems allow for reduced device preparation time, 9,10 which can significantly shorten total surgical case times and potentially increase efficiency of surgical centers and help meet the increased demand for cataract surgery. 9,[11][12][13] Preloaded delivery systems can also improve the consistency of IOL haptic folding and reduce the risk of IOL damage 9,10,14,15 by eliminating loading variability or user error and reducing the risk of contamination by eliminating the need to handle the IOL. 12,[16][17][18] A prospective, randomized, comparative study reported that the AutonoMe Delivery System provided safe and easy IOL delivery; no haptic misconfigurations were observed.…”
Section: Introductionmentioning
confidence: 99%
“…5,8 Advancements in the design of IOL delivery systems have improved efficiency and outcomes of cataract surgery, including shorter total surgical case time and reduced risk of loading variability and device contamination. [11][12][13] The automated injector system used in this study is the first preloaded delivery system to use an automated mechanism of action. It provides intuitive ergonomic single-handed control of IOL delivery designed to benefit the surgeon, such that…”
mentioning
confidence: 99%